مساهمة سوريا في إعداد الموسوعة العالمية للأبنية السكنية الواقعة في مناطق معرضة للأخطار الزلزالية برعاية و تنظيم المعهد الأمريكي لأبحاث الهندسة الزلزالية و الجمعية العالمية للهندسة الزلزالية في كندا - حويجة بسام (Latakia University Journal -Engineering Sciences Series, 2019)
This Work presents our contribution at the project entitled: An Encyclopedia of Housing Construction Types in Seismically Prone Areas of the World, supported by Earthquake Engineering Research Institute (EERI) in USA and International Association of Earthquake Engineering (IAEE) in Canada. The aim of this project is to develop a global categorization of characteristic housing and construction types in these areas, analogous to existing seismic categorizations of U.S constructions. The categorization for each housing type is presented in a standardized comparative form. The emphasis will be on identifying the structural elements of each housing type; how/if the construction type currently provides seismic resistance; and possible strengthening schemes for housing types that don’t adequately provide seismic resistance. The contribution will be aimed at local public and private organizations and individuals concerned with understanding and improving the seismic resistance of a region’s housing stock. The housing type chosen is found in the main cities of Syria. The floor system is characterized by a two-way reinforced concrete slab, which spans between orthogonal sets of beams that transfer the load to the columns; the frames are designed to carry gravity loads only. This type of building is a multiple housing unit. The following outlines summarize the intended scope of this paper: 1- General Information 2- Architectural Features 3- Socio-Economic Issues 4- Structural Features 5- Evaluation of Seismic Performance and Seismic Vulnerability 6- Earthquake Damage Patterns 7- Building Materials and Construction Process 8- Construction Economics 9- Insurance 10- Seismic Strengthening Technologies 11- Conclusions 12- References يعرض هذا العمل مساهمة سوريا في المشروع المنظم من قبل المعهد الأمريكي لأبحاث الهندسة الزلزالية (EERI) و الجمعية العالمية للهندسة الزلزالية في كندا (IAEE) . يهدف هذا المشروع إلى إعداد الموسوعة العالمية للأبنية السكنية الواقعة في مناطق زلزالية مختلفة من العالم، و يسمح بإجراء تصنيف شامل لأنظمة البناء السكني في هذه المناطق و أيضاً تحديد خواصها، بطريقة مشابهة للتصنيف المعتمد للمنشآت الواقعة في مناطق زلزالية في أمريكا. في الواقع، إن هذا العمل يتوجه إلى قطاعات مختلفة من المجتمع مثل المكاتب الهندسية الخاصة والمؤسسات والأفراد المعنيين في فهم سلوك الأبنية السكنية القائمة إزاء الأفعال الزلزالية و تحديد درجة قابليتها للتضرر، والعمل على حمايتها و تخفيف المخاطر عنها بتقويتها و تدعيمها لمقاومة الزلازل. اخترنا أنموذجاً لبناء سكني شائع الاستخدام في سوريا، موجود في الضواحي السكنية الخاصة بالعاملين في الجيش، حيث يتألف الهيكل الحامل من بلاطات مصمتة و جوائز و أعمدة مصممة لمقاومة الأفعال الشاقولية فقط. و اعتمدنا في الدراسة المحاور التالية التي حددت منهجية العمل: 1- معلومات عامة عن النموذج المعتمد 2- العناصر والخواص المعمارية 3- القضايا الاجتماعية و الاقتصادية 4- العناصر الإنشائية 5- التقييم الزلزالي 6- أنماط التضررات الزلزالية 7- مواد البناء و عمليات الإنشاء 8- اقتصاد الإنشاء 9- التأمين 10- تقنيات التدعيم الزلزالي 11- استنتاجات 12- المراجع